Some characterizations of color Hom-Poisson algebras. - ATTAN, SYLVAIN (My University, 2018)
In this paper, we describe color Hom-Poisson structures in terms of a single bilinear operation. This enables us to explore color Hom-Poisson algebras in the realm of non-Hom-associative color algebras.
Keywords: Color Hom-Poisson algebras; color Hom-flexible algebras; admissible color Hom-Poisson algebras.